2007
DOI: 10.1179/136485907x193824
|View full text |Cite
|
Sign up to set email alerts
|

Oral treatment with a potential probiotic (Enterococcus faecalisCECT 7121) appears to reduce the parasite burden of mice infected withToxocara canis

Abstract: Oral treatment with a potential probiotic (Enterococcus faecalis CECT 7121) appears to reduce the parasite burden of mice infected with Toxocara canis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 9 publications
(10 reference statements)
3
26
0
Order By: Relevance
“…In previous research, we indicated that the Ef7121 probiotic reduced the parasite burden in mice infected with T. canis (Basualdo et al 2007). In the present paper, we studied the effect of this strain on the in vitro culture of T. canis larvae and the in vivo persistence of T. canis in the murine intestine.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…In previous research, we indicated that the Ef7121 probiotic reduced the parasite burden in mice infected with T. canis (Basualdo et al 2007). In the present paper, we studied the effect of this strain on the in vitro culture of T. canis larvae and the in vivo persistence of T. canis in the murine intestine.…”
Section: Discussionmentioning
confidence: 91%
“…Ef7121 colonies were identified based on their inhibitory activity against Listeria monocytogenes CEB101 ( Sparo et al 2008). The mesenteric lymph nodes and spleens of inoculated mice were dissected and cultured to evaluate any possible bacterial translocation (Basualdo et al 2007).…”
Section: In Vivo Assaysmentioning
confidence: 99%
See 2 more Smart Citations
“…[81,82]. It has also been reported in vivo antiparasitic activity [83], immunomodulation properties [84,85], antitumor action [86] and food biopreserver [80]. AP-CECT7121 is stable at a pH range of 4.0-8.0.…”
Section: Amps Obtained From Gram-positive Bacteriamentioning
confidence: 99%